Pemanfaatan Olahan Ikan Bandeng Menjadi Nugget: Solusi Inovatif untuk Penanganan Stunting dan Peningkatan Gizi Masyarakat Pesisir Tarakan - Theresia, Theresia; Indrawanto, Denny; Yulianto, Agus; Mumtaza Putri, Anne; Nur Farida Haryanto, Lailin; Hidayat, Rezaldi; Andriyanto, Andriyanto; Warol, Khoirul; Rohasad, Rohasad; Sauri, Salsabila; Giovani Siahaan, Fery; .Gandri Haryono, M; Firdaus, Muhammad (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
This community service program presents an integrated approach to address stunting through optimization of milkfish utilization as a high-nutrition food source. Despite Tarakan's coastal area having fisheries potential reaching 2.3 tons annually, local health department data reveals stunting prevalence of 24.3%. This paradoxical situation stems from low fish consumption among toddlers (only 32% of WHO recommendation), mainly due to children's preference for instant food and parents' limited knowledge in attractive fish processing methods. The program implements participatory learning methods through three main stages: interactive nutrition education, technical fish processing training, and micro-enterprise development mentoring. Ten mothers and children actively participated in all activities. Evaluation results show significant cognitive improvement with post-test scores reaching 82 compared to 41 in pre-test. On skills aspect, 88% participants could produce quality-standard fish nuggets. The establishment of two business groups with average weekly revenue of Rp1.2 million demonstrates the program's tangible economic impact